Development of ontological support of constructive-synthesizing modeling of information systems - Skalozub, Vladislav; Ilman, Valeriy; Shynkarenko, Victor (Eastern-European Journal of Enterprise Technologies, 2017)
The methodology and means of ontological support of the processes of constructive-synthesizing modeling of complex information technologies have been developed in the study. The requirements for the applied ontology of constructive-synthesizing modeling have been formulated along with developing and specifying the conceptualization methods, axiomatics, the output system and performers that provide effective modeling for a wide range of subject areas. The theoretical basis of constructive-synthesizing modeling has been devised as the underlying principle of applied ontologies, with examples of the formation of concept models of subject domains. In ontology, constructive-synthesizing models of subject domains have been formed and presented on the basis of a single constructive structure containing primary classes of ontology instances, active binders of operators of actions and performers. It ensures universality and opportunity to use the models for developing and setting them in subject domains of modeling. The completed formalization of the ontology design allows improving the quality of automated processes of creating intelligent information technologies for structurally complex areas of modeling. This methodology is based on the paradigm of constructivism of all components of subject domains, on the revealed properties and unified models of representing concept structures, concepts and basic relations in CSM. At the same time, it has been made possible to create and maintain models of conceptual systems of subject domains that are different from taxonomy, given the uncertainties in the choice of the structure of conceptual models, both for systems of concepts of subject areas and their distinctive features